Online Travelling Planner: An Interview and Use Case Testing: An Interview and Use Case Testing - Kugan, Taruna; James, Stephen Raj; Seek Chang Liang,; Rahmat, Hazwani (Multidisciplinary Applied Research and Innovation, 2022)
This study developed an “Online Travelling Planner” based on the waterfall methodology. The online travelling planner enables tourists to plan their tour through features to book a hotel, flights, and famous locations through one platform. Traditional travel agencies incorporated with various issues that lead tourists to online travel agencies. The primary issue is the COVID-19 pandemic that restricts face-to-face interaction. Consequently, it takes the tourists a longer time to book a tour in a traditional travel agency. Use case based testing has been performed to evaluate the system functionalities. In a nutshell, an “Online Travelling Planner System” would be an alternative to be used by tourists for their tour plans.